The JMJD Family Histone Demethylases in Crosstalk Between Inflammation and Cancer - Yang, Jia; Hu, Yuan; Zhang, Binjing; Liang, Xiao; Li, Xin (Frontiers in Immunology, 2022)
Inflammation has emerged as a key player in regulating cancer initiation, progression, and therapeutics, acting as a double edged sword either facilitating cancer progression and therapeutic resistance or inducing anti-tumor immune responses. Accumulating evidence has linked the epigenetic modifications of histones to inflammation and cancer, and histone modifications-based strategies have shown promising therapeutic potentials against cancer. The jumonji C domain-containing (JMJD) family histone demethylases have exhibited multiple regulator functions in inflammatory processes and cancer development, and a number of therapeutic strategies targeting JMJD histone demethylases to modulate inflammatory cells and their products have been successfully evaluated in clinical or preclinical tumor models. This review summarizes current understanding of the functional roles and mechanisms of JMJD histone demethylases in crosstalk between inflammation and cancer, and highlights recent clinical and preclinical progress on harnessing the JMJD histone demethylases to regulate cancer-related inflammation for future cancer therapeutics.